Flores oscuras/ Sergio Ramírez - Sergio, Ramírez (Nicaragüense, 2013)
Novela Nicaragüense
Incluye: portada, índice, imágenes
Col. OGen.
Keywords: 1. OBRA GENERAL 2.NOVELA NICARAGUENSE 3. OBRA LITERARIA